Blended Learning in Academic Writing: Realities and Perspectives - KADRI, Sabah; HAMADA, Hacene (Journal of Human Sciences, 2016)
The present article is of two-fold aim. First, it undertakes a situation analysis through investigating students’ level of motivation and academic writing proficiency along with exploring teachers’ perceptions and experience with blended learning. The study, hence, hypothesizes that teachers do not fully conceive and adequately use blended learning to improve students’ academic writing performance and motivation. Second, it introduces the philosophy and methodology of blended learning in academic writing for undergraduate students, and hypothesizes that blended learning in academic writing would improve students’ motivation and academic writing performance. To test the hypotheses, questionnaires and composition tests were conducted, along with suggesting some guidelines for designing blended learning courses for language practitioners.